Regressivity of the corporate taxpayers’ compliance costs - Sapiei, Noor Sharoja; Abdullah, Mazni; Sulaiman, Noor Adwa (Elsevier Ltd., 2014)
This study evaluates the regressivity of taxpayers’ compliance costs with the corporate income tax reporting requirements.Compliance costs as a percentage of sales turnovers, ranged from 0.057% of the smallest company to 0.001% of the largest company. Larger companies were generally found to have greater compliance costs than their smaller counterparts, but as a percentage of sales, these costs were greater for smaller corporations. This study adds to the growing body of international literature concerning the distribution of compliance costs burden.Findings from these research activities should lead to the progression of more effective and efficient tax policies and practices.